EKSTRAKSI PIGMEN ANTOSIANIN DARI KULIT RAMBUTAN (NEPHELIUM LAPPACEUM) DENGAN PELARUT ETANOL - Laura Olivia Siahaan; Elvi Rasida Florentina Hutapea; Rondang Tambun (Jurnal Teknik Kimia USU, 2014)
Rambutan fruit (Nephelium lappaceum Linn) is a kind of tropical fruits which come from Malaysia and Indonesia. Their red coloured rinds have not used yet effectively and that coloured may be due to anthocyanin that can be used for natural colours. The purpose of this research is to know the optimal condition of the extraction anthocyanin, they are particle size of rambutan rinds, temperature and extraction time. Analysis of the anthocyanin use spectrophotometer UV-Vis to detect the wavelength and the absorbance of the anthocyanin. The best conditions are rambutan rind milled by blender and extraction time for 8 hours at 70 0 of temperature. These conditions give the highest color intensity having 1,0086 of maximal absorbancy, 120,1601 mg/mL of anthocyanin concentration and 0,6008 % of rendement.